Comparing multi-modality and constraint-induced treatment for aphasia: a preliminary investigation of generalisation to discourse. Issue 6 (2nd June 2016) - Rose, Miranda L.; Mok, Zaneta; Carragher, Marcella; Katthagen, Sarah; Attard, Michelle
Abstract : Background : At present, there is no consensus regarding the comparative efficacy of constraint and non-constraint treatments. Moreover, studies to date have measured the effects of treatment using single-word confrontation naming tasks and omnibus aphasia batteries. Aims : We applied reliable communicative measures of lexical and communicative behaviours to investigate the comparative impact of multi-modality aphasia therapy (M-MAT) and constraint-induced aphasia therapy plus (CIAT Plus) on three discourse genres. Methods & Procedures : Thirteen people with chronic aphasia each participated in 2 weeks of intensive CIAT Plus and 2 weeks of intensive M-MAT (30 hours over 2 weeks). Seven participants undertook CIAT Plus first, while six undertook M-MAT first. Discourse samples from three conditions were collected (picture description, Cinderella story retell and semi-structured conversation) at three time points (pre-treatment, post-CIAT Plus and post-M-MAT). Primary outcome measures included lexical measures (total words, words per minute) and communication measures (total correct information units (CIUs), CIUs per minute). Outcomes & Results : Results varied considerably within and across participants and also across the three discourse conditions. Furthermore, changes in both positive and negative directions were evident throughout the data set. There was a slight trend for better outcomes from CIAT Plus for individuals with mild aphasia and from M-MAT for individuals with moderate aphasia. Conclusions : In order to inform clinical practice and facilitate treatment planning and evaluation, further research is essential to continue to develop reliable discourse measures; to reach consensus on what constitutes "meaningful change" within discourse data and to take steps to mitigate against the variability inherent within discourse.